Multiple functions of HMGB1 in cancer - Lv, Guangyao; Yang, Menglin; Gai, Keke; Jia, Qiong; Wang, Zhenzhen; Wang, Bin; Li, Xueying (Frontiers in Oncology, 2024)
High mobility group box 1 (HMGB1) is a nuclear DNA-binding protein with a dual role in cancer, acting as an oncogene and a tumor suppressor. This protein regulates nucleosomal structure, DNA damage repair, and genomic stability within the cell, while also playing a role in immune cell functions. This review comprehensively evaluates the biological and clinical significance of HMGB1 in cancer, including its involvement in cell death and survival, its potential as a therapeutic target and cancer biomarker, and as a prosurvival signal for the remaining cells after exposure to cytotoxic anticancer treatments. We highlight the need for a better understanding of the cellular markers and mechanisms involved in the involvement of HMGB1in cancer, and aim to provide a deeper understanding of its role in cancer progression.